1999
DOI: 10.1046/j.1365-3059.1999.00310.x
|View full text |Cite
|
Sign up to set email alerts
|

The teleomorph stage, Mycosphaerella graminicola, in epidemics of septoria tritici blotch on winter wheat in the UK

Abstract: Earlier studies have shown that primary infections of winter wheat crops by septoria tritici blotch are initiated in autumn by air‐borne ascospores of the teleomorph stage, Mycosphaerella graminicola, which originate from sources outside the crop. Subsequent disease development within the crop, and damage to the upper leaves in summer, were commonly ascribed to the anamorph stage, Septoria tritici, which first arises from primary, ascosporic lesions and develops to give rise to splash‐borne pycnidiospores prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
71
0
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 23 publications
8
71
0
4
Order By: Relevance
“…Only 30 min of moistening stubble is necessary for ascospore release and dispersal [7]. Hunter et al [8] suggested that airborne ascospore plays the major role in epidemiology during the growing season and, together with splash dispersal spores, both have implications for the forecasting of the disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 30 min of moistening stubble is necessary for ascospore release and dispersal [7]. Hunter et al [8] suggested that airborne ascospore plays the major role in epidemiology during the growing season and, together with splash dispersal spores, both have implications for the forecasting of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Hunter et al [8] suggested that ascospores are dispersed in air currents rather than by rain splash, having important implications for risk-based decisions on disease control.…”
Section: Introductionmentioning
confidence: 99%
“…Airborne spores of fungal plant pathogens have commonly been detected and enumerated by microscopic examination of surfaces on which spores have been impacted (2,13). Sampling procedures may involve passive collection of spores by gravitational deposition (14) and/or sampling specific volumes of air with "active" spore-trapping devices (1,9,18).…”
mentioning
confidence: 99%
“…B 7-day traps have been used routinely to monitor fungal air spora (12,13,24,26) and in a wide variety of air-sampling studies (3,10). Ascospores on the Melinex spore tape were detected and quantified by immunofluorescence, as described by Kennedy et al (17).…”
mentioning
confidence: 99%
“…Yield losses caused by S. tritici in humid regions range from 30 to 50% if left uncontrolled (Ziv and Eyal, 1978;Burke and Dunne, 2006;Royle et al, 1986). The sexual ascospores represent the primary source of inoculum infecting young winter wheat plants in autumn (Gladders et al, 2001;Hunter et al, 1999). The asexual conidiospores are formed in fruiting bodies (pycnidia) and these spores represent the secondary inoculum for the epidemic spread and vertical transfer to the upper leaves in spring and summer (Gladders et al, 2001;Palmer and Skinner, 2002;Royle et al, 1986).…”
Section: Introductionmentioning
confidence: 99%